Analisis Pengaruh PAD, Dana Perimbangan dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah - Ala Rowanda; Baiq Ismiwati (Forum Kerjasama Pendidikan Tinggi, 2026)
The urgency of this research lies in the importance of local government financial performance as an indicator of the region's ability to manage financial resources effectively and efficiently. This study aims to analyze the effect of Local Own-Source Revenue (PAD), balancing funds, and capital expenditure on the financial performance of local governments in regencies/cities in West Nusa Tenggara Province. Data collection methods were carried out through documentation and literature review sourced from local government financial reports as well as data obtained from the Directorate General of Fiscal Balance (DJPK) website. The type of data in this study is quantitative data, which is processed using the panel data regression method to analyze the relationships between the variables studied. The research results indicate that partially, Local Own-Source Revenue has a positive and significant effect on the financial performance of local governments with a coefficient of 0.703146, which indicates that every 1% increase in PAD will increase the Fiscal Independence Ratio by 0.70%. Conversely, Balancing Funds have a negative and significant effect with a coefficient of -0.246675, where every 1% increase in Balancing Funds will decrease the Fiscal Independence Ratio by 0.24%. Similarly, Capital Expenditure has a negative and significant effect with a coefficient of -0.135521, where every 1% increase in Capital Expenditure will decrease the Fiscal Independence Ratio by 0.13%. Simultaneously, Local Own-Source Revenue, Balancing Funds, and Capital Expenditure together have a significant effect on the financial performance of regional governments in regencies/cities in West Nusa Tenggara Province with an Adjusted R-squared value of 97.99%, while the remaining 2.01% is influenced by variables outside the research model.